Patterns of library use by U.P. Rural High School students - Gapud, Lourdes P. (1985)
The main objective of this study was to determine the nature and extent of library use by the University of the Philippines Rural High School (UPRHS) students by year level, sex, proximity of residence, and academic performance. The study looked into the reasons for library use or non-use, the subjects for which the library was most used, the library materials consulted or read, the materials wanted but not available, and the materials recommended to be added to the UPRHS Library collection. Use of the UPRHS Library as well as of the Main Library of the University of the Philippines at Los Baños (UPLB Library) was investigated.